Answer:
(- 5, - 1 )
Step-by-step explanation:
Given the 2 equations
x - 3y = - 2 → (1)
2x - 3y = - 7 → (2)
Multiplying (2) by - 1 and adding to (1) eliminates the term in y
- 2x + 3y = 7 → (3)
Add (1) and (3) term by term
(x - 2x) + (- 3y + 3y) = (- 2 + 7) and simplifying gives
- x = 5 ( multiply both sides by - 1)
x = - 5
Substitute x = - 5 into (1) or (2) for corresponding value of y
Substituting in (1) gives
- 5 - 3y = - 2 ( add 5 to both sides )
- 3y = 3 ( divide both sides by - 3 )
y = - 1
Solution is (- 5, - 1 )